GAMBARAN PENDERITA THALASEMIA DI RUANG RAWAT ANAK RUMAH SAKIT UMUM CUT MEUTIAACEH UTARA TAHUN 2012 - Fatmasyithah, Vina; Sri Rahayu, Mulyati (Jurnal Edukasi dan Sains Biologi, 2014)
One of public health indicator is child mortality. One of the diseases which are prevalent in the age of the child and to be one of the death cause in children is thalassemia. In Rumah Sakit Umum Cut Meutia there is an increase in the number of patients with thalassemia from year to year. This study aims to describe patients with thalassemia in the child care room of Rumah Sakit Umum Cut Meutia Aceh Utara in 2012. This research is a descriptive cross-sectional approach. The number of samples taken 45 patients who meet the inclusion and exclusion criteria that have been determined. Data was collected using medical records to find a description of thalassemia patients based on several variables. The result showed that the highest proportion of patients with thalassemia is 5-12 years of age (60%), male (51.1%), derived from 13 districts in Aceh Utara (75.6%) and outside Aceh Utara (24.4%), type of ? thalassemia (57.8%), pale as chief complaint (80%), management of transfusion and pharmacological (51.1%), poor nutritional status (64.4%). Recording of family history variables are not present in all patients with thalassemia in RSU Cut Meutia in 2012, thenexpected to the RSU Cut Meutia to complete the recording of the medical records, especially recordingfamily history variables.Keywords: Overview of patient, Thalassemia, Family History, Nutritional Status